Cantilever Bridge Design as Esthetic Restoration on Post Endodontic Treatment: Case Report - Fatmawati, Dwi Warna Aju (The Indonesian Journal of Dental Research)
In dentistry, aesthetic and cosmetic had become patient demands, because it was related with beauty. In aesthetic restorative and cosmetic treatment, dentists were not only concerned in beauty but also must consider function of restoration. Thus, dentists must select materials and designs that had ability on occlusion and mastication bearing for long time in oral cavity. Dentures or restoration treatment that had similar color with tooth was known for a long time, because it can improve aesthetic and self-confidence. The aim of this case report was to explore aesthetic restoration used in cantilever bridge on post endodontic treatment subject. This bridge can be used as a more simple alternative treatment for subject whose restorative was broken and used partial denture.Â